Closing the gap for efficient immobilization of biocatalysts in continuous processes: HaloTag™ fusion enzymes for a continuous enzymatic cascade towards a vicinal chiral diol. Issue 2 (4th January 2018) - Döbber, J.; Gerlach, T.; Offermann, H.; Rother, D.; Pohl, M.
Abstract : Compartmentalization of biocatalysts is an effective tool to integrate biocatalytic steps in continuous (chemo)enzymatic cascades. Abstract : Compartmentalization of biocatalysts is an effective tool to integrate biocatalytic steps in continuous (chemo)enzymatic cascades. Therefore, efficient covalent immobilization techniques are of utmost importance, which enable a fast and selective immobilization of the enzyme directly from crude cell extracts. Here we demonstrate that the HaloTag™ mediates the covalent immobilization of such fusion enzymes in only a few minutes contact time with the respective modified carrier in a packed-bed reactor, thereby enabling enzyme immobilization directly in the flow setup. In this study, we evaluated this concept for a continuous enzymatic cascade towards a chiral vicinal diol by combining a variant of the benzoylformate decarboxylase from Pseudomonas putida ( Pp BFD) and the alcohol dehydrogenase from Lactobacillus brevis ( Lb ADH). Limitations in Pp BFD stability were overcome by optimization of buffer salt, cofactor concentration and choice of a different substrate. For optimal Lb ADH activity, excess acetaldehyde was removed in-line. This optimization lead to a high operational stability of the individual cascade steps up to several weeks and resulting in the efficient stereoselective production of (1 S, 2 S )-1-phenylpropane-1, 2-diol with high conversion up to 99%, high stereoselectivities (ee/ic) up to 96% and space–time yields up to 1850 g L −1 d −1 .